DO PERIPHERAL AND EXTRA MUSCULOSKELETAL MANIFESTATIONS HAVE AN IMPACT ON BIOLOGIC DMARD PRESCRIBING PATTERNS IN AXIAL SPONDYLOARTHRITIS: THE RESULTS OF TREASURE EXPERIENCE - Ediboglu, E. Durak; Solmaz, D.; Karadag, O.; Pehlivan, Y.; Cinar, M.; Ertenli, A. I.; Akar, S. (Elsevier, 2021)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 02-05, 2021 -- ELECTR NETWORK